Prediction of early race starts in Norwegian-Swedish Coldblooded Trotters - Ihler Carl F; Larsen Stig; Revold Tobias (Acta Veterinaria Scandinavica, 2010)
Abstract Background Less than a third of Norwegian-Swedish Coldblooded Trotters (NSCTs) have started racing as three year olds since the year 2000 despite the fact that large sums are paid out as price-money in the three year season. Recruitment races are arranged by the Norwegian Trotting Association (NTA) to stimulate early training. The management of young horses varies considerably and a large majority is reared by amateurs. The aim of the present study was to identify predictors of early race starts in young NSCT horses under field conditions. Methods Of the 801 registered NSCT horses born in 2005, 144 were randomly selected by stratified sampling with gender and paternal progeny as stratification factors. All horses were examined clinically. Further data were collected from NTA and by interviews of breeders, owners and trainers. The set of dependent variables consisted of "passed recruitment race", "start in regular race by the end of the three year season" and "start in regular race by the end of October in the four year season". Univariate and logistic regression analyses were performed. Results Genetic performance potential, as indicated by best linear unbiased prediction (BLUP) indices, was the major predictor of the three dependent variables despite large variation in management. Dam's index was a better predictor than sire's index. However, the probability of early race starts in a horse with a low genetic performance potential can be increased by a favourable management. Examples of advantageous management factors in the present study were a flat pasture the first summer and early training. Nearly all horses racing in the three or four year seasons had passed a recruitment race in the two year season. Conclusions The results confirm the value of the published BLUP index as an important tool for the NSCT breeding program. Recruitment races stimulate early training.